Investigating Vegetation Responses to Underground Nuclear Explosions Through Integrated Analyses. Issue 5 (10th May 2021) - Solander, Kurt C.; Collins, Adam D.; Swanson, Erika; Margolis, Ellis Q.; Crawford, Brandon; Miller, Elizabeth; Chen, Min; Lavadie‐Bulnes, Anita; Ryan, Max; Borrego, Isaac; Sevanto, Sanna; Schultz‐Fellenz, Emily
Abstract: Vegetation has the potential to respond to underground nuclear explosions, yet these links have not been fully explored. Given the lack of previously described signatures, the changes in vegetation are possibly subtle. The integration of multiple different data streams is potentially a useful approach to improve signal detection. Here, we investigate whether semi‐arid vegetation growth patterns responded to eight legacy underground nuclear tests at the Nevada National Security Site in southern Nevada, USA. We tested for spatial and temporal changes in vegetation cover, tree growth patterns, and tree leaf spectral properties using ground‐based measurements, including those from tree‐rings and hyperspectral surface vegetation reflectance, as well as space‐based measurements of Normalized Difference Vegetation Index (NDVI) from Landsat. Multiple data streams suggest a localized (<1.2 km) spatial pattern whereby tree growth is enhanced closer to the source of the underground test relative to sites further away. We also observed a more regional (>1.2–9 km) pattern whereby tree growth is suppressed coincident with a drought beginning 1 year before the 1989 tests, but continuing in the 5 years following the tests, which is anomalous relative to what is expected based on the response of tree growth to previous droughts. Quantification of the relative effects of the tests on vegetation remains a challenge due to the coincident drought and the potential for other disturbances to have impacted tree growth at this time, but the integration of these data reveals a more nuanced growth response than any other one data set indicates alone. Key Points: Vegetation signatures suggest localized increased vegetation growth patterns following underground nuclear explosion within 1.2 km of source More regional (up to 9 km) reduced pattern in vegetation growth likely related in‐part to a multiyear drought over southern Nevada, USA Impacts on vegetation from drought combined with the explosions were more severe than expected when compared to other droughts of greater magnitude